2014
DOI: 10.1021/pr500807t
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS-Based Urinary Metabolite Signatures in Idiopathic Parkinson’s Disease

Abstract: Increasing evidence has shown that abnormal metabolic phenotypes in body fluids reflect the pathogenesis and pathophysiology of Parkinson's disease (PD). These body fluids include urine; however, the relationship between, specifically, urinary metabolic phenotypes and PD is not fully understood. In this study, urinary metabolites from a total of 401 clinical urine samples collected from 106 idiopathic PD patients and 104 normal control subjects were profiled by using high-performance liquid chromatography coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 65 publications
9
106
0
Order By: Relevance
“…LC‐MS has been widely used in metabolomics research . The major SMMs analytes for LC‐MS include polar compounds, non‐volatile compounds, and thermo‐unstable compounds.…”
Section: Technology Advancement Of Mass Spectrometry‐based Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…LC‐MS has been widely used in metabolomics research . The major SMMs analytes for LC‐MS include polar compounds, non‐volatile compounds, and thermo‐unstable compounds.…”
Section: Technology Advancement Of Mass Spectrometry‐based Metabolomicsmentioning
confidence: 99%
“…Advances in techniques have stimulated a great interest in the application of metabolomics to explore neurodegenerative disorders, including Parkinson's disease (AD), Alzheimer's disease (PD), Huntington's disease (HD), and amyotrophic lateral sclerosis (ALS) . Applications of metabolomics have revealed novel SMMs in biological samples such as cerebrospinal fluid (CSF), plasma, serum, urine, and stool collected from PD or AD patients and animals by using multiple mass spectrometry (MS)‐based platforms . Analysis of SMMs has not only contributed for better understanding the mechanisms of the development of diseases, but also helped discovering new biomarkers for diseases diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The validly large scale of human samples in biomarker discovery studies effectively averages out substantial variations observed in the human metabolome that are caused by differences in age, gender, diet, medication, lifestyle, stress and many additional factors Mapstone et al 2014;Mayers et al 2014). Recent studies have advanced the application of the liquid chromatography-mass spectrometry (LC-MS) technique to large-scale studies of human biofluid samples (such as serum, plasma, and urine) Mapstone et al 2014;Luan et al 2015). The untargeted metabolic profiling of one sample can be completed within a few minutes, enabling an analytical throughput of [100 samples per day (Evans et al 2009;Lv et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These indicate that the level of 8-OHdG in urine could be a good indicator of oxidative damage to DNA in the whole body. Although some urinary chemical constituents are affected by diet, exercise, hormone status and other physiological conditions, and high concentrations of urea and inorganic salts (chloride, sodium, and potassium) in urine may result in ionization source contamination and ion suppression in mass spectrometry detection, compared with other biological matrices such as plasma, serum and saliva, urine has long been considered to be a preferred diagnostic biofluid in clinical practice since it is sterile, easily obtainable in large volumes, and noninvasive to patients272829303132. Therefore, urinary 8-OHdG analysis should be the first choice for disease risk evaluation, early detection, treatment and prognosis.…”
mentioning
confidence: 99%